Isolation and characterization of avian leukosis virus subgroup J associated with hemangioma and myelocytoma in layer chickens in China - Wu, Lan; Li, Youjun; Chen, Xueyang; Yang, Yuxin; Fang, Chun; Gu, Yufang; Liu, Jing; Liang, Xiongyan; Yang, Yuying (Frontiers in Veterinary Science, 2022)
The first strain of avian leukosis virus subgroup J (ALV-J) emerged in 1987 as a new subgroup of avian leukosis and spread rapidly throughout the world. The poultry industry had suffered significant losses because of ALV-J. Even though the disease has been prevented and controlled by culling infected chickens, cases of avian leukosis continue to be reported. In this study, an ALV-J strain named as HB2020 was isolated from egg-type chickens in Hubei Province. Full-length proviral genome sequence analysis revealed that HB2020 was a recombinant strain of ev-1 and HPRS-103 in the gag region when compared to HPRS-103. In the 3'UTR, there were 205 bp deletions, 175 of which were in the rTM region. Gp37 was relatively conservative, whereas gp85 had five conservative site mutations. Animal experiments revealed that HB2020 can cause a variety of tumor diseases in chickens, including enlarged liver with hemangiomas and spleens with white necrosis. The number of myelocyte-like tumor cells in the blood smears of infected chickens increased gradually as the exposure time increased. As a result, our findings suggest that HB2020 was recombined by ALV-E and ALV-J, potentially causing severe hemangiomas and myelocytomas. The above conclusion may provide a molecular basis for further research into ALV pathogenicity and alert people to the importance of avian leukosis control and prevention.